Management Strategies for the Automotive Parts Industry in Thailand - Patcharawattanakul, Viroj; Niyomyaht, Satit; Kalyanamitra, Kamolporn (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
This research aimed 1) to study the operational problems of the automotive parts industry in Thailand, 2) To study the demand of entrepreneurs in the automotive parts industry in Thailand. 3) propose a more appropriate management approach for the role of the automotive parts industry in Thailand. This research was conducted by collecting and analyzing qualitative data, involving the collection and analysis of data through in-depth interviews. Key informants included representatives from government policy agencies, automotive parts industry operators, and 20 electric vehicle users, selected through purposive sampling. The primary research instrument was a semi-structured interview guide. Data were analyzed using content analysis and presented in a descriptive format. The research found that 1) Most of the problems was related to rising production costs, competition from both domestic and international markets, and limitations of modern technology. 2) Demand for to elevate the domestic automotive parts industry, which used to rely on combustion engine production, to a new vision that emphasizes more innovation and sustainability in order to maintain competitiveness in the global market and support technological changes. 3) Management Strategies for the Automotive Parts Industry in Thailand include: 3.1) Required a comprehensive strategy encompassing economic factors, technological development, and environmental sustainability. 3.2) Involved investment in new technologies, such as electric vehicle (EV) components and clean energy technologies Article history: Received 15 May 2025 Revised 28 June 2025 Accepted 30 June 2025 SIMILARITY INDEX = 12.23 %